Social Protection in the Philippines: Current State and Challenges - Aniceto Jr. C. Orbeta (Philippine Institute for Development Studies (PIDS), 2011)
This paper reviews the current state of and challenges facing social protection in the Philippines. It describes the social protection institutions and the schemes that have been developed throughout the years. It also provides an assessment focusing on coverage, administration, and management. The paper then lists several reform themes for the country's social protection system.The paper finds a continuing low coverage of the main bulk of workers - formal private sector wage-workers - even if the system expanded statutory coverage to own-account, overseas, domestic workers, and even housewives. The lack of coverage of informal sector workers persists. There is a continuing threat to sustainability because contributions and benefits are not strongly linked, particularly for the SSS. The funds are also subjected to continuous political pressure to finance social programs that are of doubtful return and which may not be in line with the long-term nature of the fund's obligations. There is also a need to continuously improve the investment earnings of the reserve funds. This may include terminating programs which are unlikely to meet the earning requirements for actuarial viability. Finally, there is a need to examine the increasing operating costs, considering that these are among the highest in the region.
Keywords: H55; 330; social security; Philippines; social protection; Soziale Sicherheit; Sozialversicherung; Armut; Sozialpolitik; Philippinen